Paradoxical adverse drug reactions: descriptive analysis of French reports - Hakimi, Yan; Petitpain, Nadine; Pinzani, Véronique; Montastruc, Jean-Louis; Bagheri, Haleh (European journal of clinical pharmacology, 2020)
Introduction Paradoxical adverse drug reactions (ADRs) are defined as being opposing reactions to the pharmacological effect of drugs in relation to its pharmacodynamic properties. Their diagnosis is difficult as they are relatively rare with atypical clinical presentation (with the possibility of being confused with drug ineffectiveness or the worsening of the underlying disease). This kind of ADR may be particularly subject to under-notification. The aim of the present study is to describe paradoxical ADRs using the French PharmacoVigilance DataBase (FPVDB). Method We analysed all reports recorded in the FPVDB with drugs defined as “suspect” and which included the term “paradoxical reaction” (PR) (according to MedDRA classification) from 01/01/1984 to 12/31/2018. The drugs were classified according to the Chemical Therapeutic Anatomical Classification (ATC). Results We found 57 reports of PR, with half of them recorded between 2015 and 2018. The median age of patients was 46 years, mainly male (54%). The most frequently involved drugs were immunomodulating agents ( n = 28, 49%) and psychotropics ( n = 28, 49%). The leading paradoxical ADRs were psychiatric (anxiety, sleep and behavioural disorders) and skin-related. In 19 cases (33%), PR was related to benzodiazepines mainly occurring in patients in extreme ages (five cases in children and patients > 70, respectively, 53%). For psychotropic-induced PR ( n = 28), known contributory factors (alcohol consumption, underlying psychiatric diseases) were found in 18 cases (64%). Paradoxical reactions with immunomodulating agents were mainly related to skin ADRs ( n = 25). For psychotropics, paradoxical ADRs occurred rapidly after a mean delay of 1 day, predominantly following high doses. We also identified several “unexpected” paradoxical reactions, such as cognitive degradation with donepezil, or a return to impulsive smoking addiction with varenicline. Conclusion This study highlights that pharmacovigilance databases like the French database make it possible to investigate the main characteristics of paradoxical reactions to drugs. This ADR was mainly found in the FPVDB with psychotropic drugs and immunomodulating agents. Moreover, pharmacovigilance databases enable the identification of some signs of “unexpected paradoxical reactions”. In order to identify this type of ADR more effectively, work on awareness and harmonization is required to register these reports. The addition of the term “paradoxical reaction to the drug” to the list of other symptoms would facilitate their identification and analysis.